Design and Analysis of Harmonic Reducer Combined Curve Cam Wave Generators - Mu Man; Tao Menglun; Liu Bin; Chen Dingfang; Wu Junfeng; Zhang Huiming; Hu Qunfei (Jixie chuandong)
The shape of wave generator directly affects the mechanical characteristics of the flexspline. Flexspline is the weakest part of harmonic drivers. In order to improve its life, the design of a cam wave generator based on a conical curve combination is introduced. The combined curve cam is composed of a parabola, a connecting arc and an eccentric arc; the smooth transition between the parabola, the connecting arc and the eccentric arc is taken as the constraint conditions. The influence degree of each parameter on the maximum equivalent stress of the flexspline is calculated and analyzed by orthogonal experiment, and the curve parameters of each section of the combined curve cam wave generator are determined. The transient dynamic analysis of the flexspline under the action of standard elliptic cam and combined curve cam is carried out using the finite element software, and the fatigue life of the flexspline is studied using the transient dynamic analysis results based on the nCode-Designlife software. The results show that the maximum equivalent stress of the flexspline is lower than that of the standard ellipse cam wave generator, under the action of combined curve cam wave generator, the stress at the front and back ends of the tooth ring in the meshing area of the flexspline is obviously reduced, the stress distribution is more uniform, and the fatigue life is also improved.